Mary Magdalene: a biography - Chilton, Bruce (Doubleday, 2005)
Marguerite -- Possessed -- The Magdalene -- Secret exorcism -- Mary's signature -- Nameless anointer -- "Thy name is as oil poured forth" -- Transfiguration at the tomb -- Ecstatic vision -- The scar -- Expurgating the Magdalene -- Orthodox ambivalence and the gnostic quest -- The breakout -- The goddess and the vixen -- Relics of the Magdalene